The Fusion of Smartphone Sensors for Indoor 3D Position and Orientation Estimation - Hani Ramadhan; Charles Lenay; Dominique Lenne (IPTEK Journal of Proceedings Series, 2015)
The improvement in smartphone technology has encouraged the exploration in field of user experience. The internal inertial navigation system sensors of a smartphone enables it to infer the its three dimensional indoor orientation and position when it is being pointed at certain objects by hand. However, the sensors’ flawed measurements complicate estimation of position and orientation precisely. Previous studies shows that sensor fusion of both internal and external measurements can enhanced the performance. However, those estimations didn’t cover the pointer-like usage. To achieve the possibility of smartphone as pointer, the estimation using sensor fusion has been performed. Unfortunately, these experiments resulted in bad position estimation for small precision, while the orientation estimation was passable